2018
DOI: 10.1002/pssb.201800215
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure Factors of Aqueous Mixtures of 1‐Propanol and 2‐Propanol: X‐Ray Diffraction Experiments and Molecular Dynamics Simulations

Abstract: The structure factor of pure 1‐propanol, 2‐propanol, and mixtures of 1‐propanol/water and 2‐propanol/water, as a function of composition, has been determined experimentally and by molecular dynamics simulations. The primary aim is to find interatomic potentials that reproduce measured structural data at the highest possible level. For this reason, various alcohol potential models have been employed, including united atom (UA) and all atom (AA) types, in combination with a TIP4P‐based model for water. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…There are several works that explore the structural and dynamical properties of isopropanol/water liquid mixtures using molecular dynamics simulation 12,23,30 . These simulations showed that recently employed force fields provide acceptable agreement over a wide composition range between calculated and measurable physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…There are several works that explore the structural and dynamical properties of isopropanol/water liquid mixtures using molecular dynamics simulation 12,23,30 . These simulations showed that recently employed force fields provide acceptable agreement over a wide composition range between calculated and measurable physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The structure factors calculated from CPMD simulations were also compared with the experimental neutron/X-ray structure factor data for propanol, butanol, and pentanol (Supporting Information, Figure S4). The fact that the rdfs and structure factors obtained from ab initio MD simulations are comparable with the experimental data gives us the confidence that simulations are representative of the liquid state of alcohols.…”
Section: Simulation Methodologymentioning
confidence: 66%
“…Core electrons were treated using the norm-conserving atomic pseudopotentials of Troullier–Martins, while valence electrons were represented in a plane-wave basis set truncated at an extended energy of 70 Ry . A 70 Ry cutoff has been widely used in the literature and has been considered as adequate in most studies. , The value of the cutoff is a trade-off between accuracy and computational time required per MD step (see the Supporting Information, Figure S1). Before the ab initio molecular dynamics simulations, a classical MD (using Materials Studio software) simulation was run using universal force field (UFF) parameters.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…In the AA model, the structure factors for pure substances in the original and the modified force fields were compared with the experimental spectrum obtained by X-ray diffraction [29], Fig. 2A.…”
Section: Structure Factor and Bond Distancementioning
confidence: 99%